Utilizing Photovoice to Support Indigenous Accounts of Environmental Change and Injustice - Felicia M. Mitchell; Shanondora Billiot; Stephanie Lechuga-Peña (Genealogy, 2020)
Global environmental changes can happen quickly or over extended periods and have compounding effects. Indigenous communities experience environmental changes that can lead to a decline in quality of life, illness or disease, and unwelcome cultural adaptations that extend to future generations. Due to limited resources and political marginalization, members of these communities may not be able to respond to or prevent these conditions. Cultural connections to the land and community, along with limited resources, impact Indigenous peoples’ willingness and ability to relocate to different geographic locations experiencing less damaging ecological changes or environmental risk. In this article, we respond to the Special Issue prompt probing “[m]ethods in which Indigenous communities engage within their environment and on the land to conduct research”. We begin by describing environmental change, followed by a scoping review of Photovoice studies focused on environmental issues. Environmental changes affecting Indigenous groups are discussed, including a case study and a discussion of the ways that Photovoice can support and honor Indigenous peoples’ connection to the natural environment. This article is not intended to be an exhaustive review, but rather seeks to understand how Photovoice is being used to respond to and document environmental change, and how such visual methodologies can be used in Indigenous communities.